Amino-functionalized vertically ordered mesoporous silica film on electrochemically polarized screen-printed carbon electrodes for the construction of gated electrochemical aptasensors and sensitive detection of carcinoembryonic antigens - He, Ke; Wang, Hongxin; Luo, Tao; Yan, Fei; Guo, Jing (Frontiers in Chemistry, 2024)
Disposable electrochemical biosensors with high sensitivity are very fit for point-of-care testing in clinical diagnosis. Herein, amino-functionalized vertically-ordered mesoporous silica films (NH2-VMSF) attached to the electrochemically polarized screen-printed carbon electrode (p-SPCE) are prepared using a simple electrochemical method and then utilized to construct gated electrochemical aptasensor for rapid and sensitive determination of carcinoembryonic antigen (CEA). After being treated with the electrochemical polarization procedure, p-SPCE has plentiful oxygen-containing groups and improved catalytic ability, which is helpful for promoted stability of NH2-VMSF on SPCE without the use of adhesive layer and simultaneously generates highly electro-active sensing interface. Owing to the numerous uniform and ultrasmall nanopores of NH2-VMSF, CEA-specific aptamer anchored on the external surface of NH2-VMSF/p-SPCE serves as the gatekeeper, allowing the specific recognition and binding of CEA and eventually impeding the ingress of electrochemical probes (Fe(CN)6 3-/4-) through the silica nanochannels. The declined electrochemical responses of Fe(CN)6 3-/4- can be used to quantitatively detect CEA, yielding a wide detection range (100 fg/mL to 100 ng/mL) and a low limit of detection (24 fg/mL). Moreover, the proposed NH2-VMSF/p-SPCE based electrochemical aptasensor can be applied to detect the amount of CEA in spiked human serum samples, which extends the biological application of disposable NH2-VMSF/p-SPCE sensor by modulating the biological recognition species.